Preparation, X-ray Structure, and Reactivity of 2-Iodylpyridines: Recyclable Hypervalent Iodine(V) Reagents - Yoshimura A. Akira; Banek С. T.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Nemykin V. N.; Zhdankin V. V. Viktor Vladimirovich (2011, 2011)
Title screen